Observação e generalização de padrões: um tema para a investigação de professores sobre sua própria prática - Santos, Juliana Grassmann dos (2008)
The present study investigated which are the changes in the teachers perception about the theme Observation and Generalization of Patterns when living a research process in his/her own classroom. The data of the research were obtained from the observation and intervention in the processes of research-action of two teachers. These teachers participated in a course of continuous formation proposed by the Project of Valorization of the Educator and Improvement of the Quality of Teaching of the municipal net of schools of São Paulo and they have conducted researches in their own classroom referring to observation activities and generalization of patterns. The collected data point to a variety of learning methods, some of them directly related to the theme of the group, the observation and generalization of patterns, and others related to the research methods privileged in the group, the research into the own practice using the methodology inspired in the didactic engineering. The teachers noticed the importance of the theme and they started locating subjects that involve patterns inside of their class, regarding them as part of their school routine. There are statements in which the teachers mention the great interest shown by the students when solving such activities and their willingness to indicate subjects of the book that were previously unknown by them. There was a visible change in the teachers' viewpoint during the analysis of the protocols, since they have stopped classifying the students as being right or wrong and have started to observe and to understand the reasoning that was being used by the students. The investigation of patterns in sequences revealed to be an including and stimulant theme to the teachers. Furthermore, the research-action accomplished by teachers side-by-side with researchers for a period of time revealed to be a favorable atmosphere to changes and to the professional improvement of all the involved